Locally-led adaptation: Moving from principles to practice in the water sector - Claire Bedelian; Judith Mulwa; Beatrice Sumari; Peter Rogers; Marie Ladekjær Gravesen; Mikkel Funder (Danish Institute for International Studies (DIIS), 2024)
Climate change adaptation is a major global challenge and key to securing livelihoods and economies in the Global South. Locally-led adaptation (LLA) is gaining momentum as an approach to integrate local context, address equity concerns, and enhance the efficiency of adaptation efforts. This study focuses on LLA in the water sector, examining progress and lessons learnt from water adaptation initiatives in East Africa's drylands. The report introduces an assessment framework to evaluate how case studies of water adaptation align with the LLA principles, supplemented with a principle on Nature-based Solution (NbS) in recognition of its potential in locally-led water adaptation. The framework is then applied to six water adaptation case studies in Kenya and Tanzania. It focuses on the governance and finance processes that prioritise the agency of local actors, and explores the adaptation outcomes, emerging social and environmental impacts, benefits, and sustainability of interventions.
Keywords: 300; Water governance; Nature-based solutions (NbS); Locally-led adaptation (LLA); water adaptation; Kenya; Tanzania